Three-dimensional Stress Analysis Study on Multi-Bolted Joints of Composite Plates - Supar, Khairi; Ahmad, Hilton; Sim Yee, Lee (International Journal of Engineering and Technology, 2018)
Single-lap bolted joint is the widely applied technique in joining parts of aerospace and civil engineering structures, due to joint efficiencies where staggered arrangements are commonly adopted. This particular joint type exhibits secondary bending phenomenon due to eccentric loading path. Stress analysis enables the structure engineers to predict the failure path and maximum stress that may lead to catastrophic failures. Stress analysis study were carried out in multi-bolted woven fabric kenaf reinforced polymer (WKRP) joints with variation of lay-up types, hole configurations and plate thicknesses. 3-D FEA modelling implemented here explicitly incorporates out-of-plane deformation to provide better prediction upon crack initiation from maximum stress exhibited along the hole boundary. WKRP plates tested were failed in net-tension where the crack propagated normal to its applied stress. It was found that plate variation (i.e., lay-up types, hole configurations and plate thicknesses) correspondingly affect tangential stress distributions along its hole boundary. Current 3-D models used modulus properties from independent experimental work which regarded as smeared-out properties through their plate thickness. Staggered configurations demonstrated more evenly stress distribution to their adjacent bolts due to stress resistance diagonally and larger staggered plate width. Slightly contrast in lay-up types where larger tangential stress is exhibited in cross-ply due to more volume fraction of 0Â° fiber direction. Larger tangential stress in thicker plates associated to effective friction stress transfer to give higher failure load. Effects of secondary bending is more prominent in cross-ply and thinner plates, assumption of smeared-out properties is less good due to plate edge lifting, however, effect of secondary bending phenomenon in multi-bolted is lesser than single-bolted joints.Â Â